A titanium dioxide–carbon nanotube hybrid to simultaneously achieve the mechanical enhancement of natural rubber and its stability under extreme frictional conditions. Issue 7 (15th March 2021) - Wan, Le; Deng, Cong; Zhao, Ze-Yong; Zhao, Hai-Bo; Wang, Yu-Zhong
Abstract : Titanium oxide-carbon nanotube hybrids may efficiently promote the stability of nature rubber under extreme frictional conditions. Abstract : Currently, carbon black as an efficient reinforcing agent dominates the reinforcement field of natural rubber (NR). However, its general loading amount is quite high for achieving the reinforcement of NR. In this work, titanium oxide-carbon nanotubes (TiO2 –CNTs) were prepared by using the hydrothermal method. When a small amount of TiO2 –CNTs additive was used to reinforce NR, significant mechanical enhancement was achieved. Experimental results confirmed that the tensile strength and elongation at the break of NR containing 3.0 wt% TiO2 –CNTs (NR/3TiO2 –CNTs) were 32.0 MPa and 1604%, corresponding to an increase by about 79.5% and 14.5%, respectively, in comparison with that of pristine NR. Moreover, thermal analysis confirmed that the initial decomposing temperature of NR was promoted to 313.5 °C from 287.9 °C after the incorporation of only 3 wt% TiO2 –CNTs, which was raised by 25.6 °C. An intensive friction test confirmed that the maximum temperatures at the surfaces of NR/3TiO2 –CNTs and NR/5TiO2 –CNTs were 217 and 210 °C, respectively, which decreased by 29 and 36 °C in comparison with that of NR. The study of the mechanical enhancement confirmed that the uniform dispersion of TiO2 –CNTs and superior interfacial interactions between NR and TiO2 –CNTs played a dominant role in the mechanical enhancement of NR/TiO2 –CNTs composites. For the improved stability of NR/TiO2 –CNTs composites, the physical barrier action of TiO2 –CNTs to heat and oxygen, excellent heat dispersion of CNTs, and the increased graphitization degree at the surface played a vital role. The TiO2 –CNTs show specific advantages in simultaneously reinforcing the mechanical properties of NR and promoting its stability under extreme friction condition.